Upaya Peningkatan Hasil Belajar Siswa Menggunakan Model Project Based Learning Pada Materi Teks Prosedur - Rahmadani, Fitrah (Indonesian Journal of Pedagogical and Social Sciences, 2023)
Abstract. This study examines the low results of learning English in class XI AKL 1 students of SMK Negeri 1 Pangkep. The purpose of this study was to describe the application of the Project Based Learning learning model to improve English learning outcomes in class XI AKL 1 students of SMK Negeri 1 Pangkep. This study uses a descriptive qualitative approach. This type of research is classroom action research (CAR) which is carried out in 4 (four) stages of each cycle, namely planning, implementing, observing, and reflecting. The focus of this research is the application of the Project Based Learning model and student learning outcomes. The setting of this research was class XI AKL 1 SMK Negeri 1 Pangkep, while the research subjects were one class teacher and 31 students consisting of 24 female students and 6 male students. In this study, the researcher acted as a teacher. Data analysis techniques are qualitative and quantitative. The results showed that the teacher's teaching activities in the first cycle were still in the sufficient category and in the second cycle they increased to a good category. Likewise, student learning activities in cycle I were in the sufficient category and in cycle II it increased to a good category. While student learning outcomes in cycle I were in the sufficient category and student learning outcomes in cycle II increased to a good category. The conclusion of this study is that through the application of the Project Based Learning model, the results of learning English in class XI AKL 1 students at SMK Negeri 1 Pangkep have increased Keywords: Project Based Learning (PBL), Hasil Belajar, Teks Prosedur